(3GdLhGQM ef GdHRGg hGdThGgjf hGdUbhQs - (3eMeO Hf ESMGb GdMfHdjs ((3GHQGgje Hf YHO GdeMSf Hf bQjGU GdTGgi s)
(3ChdgG (B:s
(3jHOC HHGH ai eYQaI ebOGQ WYe GdWjQ dg s
(3BNQgG (B:s
(3jfJgi CKfGA HGH ddbdGY s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs